Deteksi Dini Anak Disleksia dengan metode Support Vector Machine - Ardhian Ekawijana; Akhmad Bakhrun; Zulkifli Arsyad (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Dyslexia is a brain disorder caused by genetics. People with dyslexia can live a normal life and even have certain advantages if they get the correct education. People with dyslexia often get the predicate stupid because teachers do not know the case of their students. Early detection of dyslexic children can be done with a series of tests so that the system can conclude that the data is dyslexic or not. Support Vector Machine is a data classification method to share dyslexia test results or not. This system is trained with test results data that are already available using the SVM method. This study uses gamification data to detect dyslexic children or not. SVM proves a good level of accuracy in predictions up to 94%.